Concentration and Coherence of the Field in the Islamic State of the Caliphate from the Foundation to the End of the Umayyad Era(11-132 A.H) - .ltaief, mohamed (The Algerian Historical Journal, 2026)
Although it was based on strong administrative structures, the empire of early Islam was not a coherent building in which the relationship of the center to the parties was integrated in a clear and organized way, as is the case with the empire of the Romans or others. In addition to the division of the imperial space into eastern and Maghreb wings, each province enjoyed a great deal of independence derived from the presence of a regional administrative apparatus and the absence of a precise formula between it and the administration in the center. These divisions, at the heart of the imperial sphere, led to the growing role of some intermediary states, such as Egypt and Iraq, as they became administratively and politically supervising vast areas, thus forming a multi-centered empire that lacks coherence and harmony.